Fabrication of Magnetite Nanoparticles With Hydrophobic Imidazolium Ionic Liquid for the Efficient Role in Oil Spill Collection - Abdelrahman O. Ezzat; Mohd Sajid Ali; Noorah A. Faqihi; Hamad A. Al-Lohedan (Journal of Chemistry)
As one of the main environmental obstacles, oil spill causes serious consequences on the environment, fauna, and flora. The traditional methods for cleaning up oil spills were found time-consuming, expensive, and ineffective. Magnetite nanoparticles have attracted great attention as alternatives to the conventional methods as a result of the substantial efficiency, quick controlling, and remedying of oil spills. In the present work, trisubstituted imidazole was prepared by one-pot reaction followed by alkylation with tetradecyl bromide to obtain hydrophobic 4,5-diphenyl-1,3-ditetradecyl-2-(2-(tetradecyloxy)phenyl)-1H-imidazole-3-ium bromide, tetradecylimidazolium ionic liquid (TTIML). After that, magnetite nanoparticles were prepared and coated with TTIML in order to control the particle size and modify the magnetite surface to be hydrophobic enough to spread in the oil spill and consequently cleaning the oil by the application of an external magnet. The structures of magnetite nanoparticles coated with newly synthesized ionic liquid (TTIML-Fe3O4) was confirmed using FTIR, XRD, TEM, and DLS. Only about 10 wt% of IL was sufficient to obtain monodispersed Fe3O4 nanoparticles as confirmed by TGA thermogram. The oil spill collecting efficiency of Fe3O4 NPs reached 95.5 ± 2.9% at magnetite to oil ratios (1 : 25) which indicate its application.